Urban challenges in Dammam metropolitan area: the oil capital of Saudi Arabia - Alhajri, Mubarak Faisal (Frontiers in Built Environment, 2025)
Sustainable Development Goals (SDGs) form one of the internationally recognized frameworks that guide sustainable urban development. In line with Saudi Vision 2030, the Saudi government aims to increase the livability of Saudi cities. The aim of this study is to assess the current status of the SDG 11 key factors at the local government level in Saudi Arabia. Thus, Dammam Metropolitan Area (DMA) was selected as a case study. A questionnaire survey and a purposive sampling technique were utilized to assess the SDG 11 key factors. The Relative Importance Index (RII) was utilized as a technique to analyze the collected data and establish the most significant challenging factors within the city level based on feedback from public sector stakeholders. The study found that the most challenging SDG 11 key factors in DMA are first, SDG 11.1 Access to safe, affordable, accessible, and sustainable transport systems for all, with RII (0.845); second, SD G11.7 Universal access to safe, inclusive, and accessible green and public spaces, with RII (0.809); and third, SDG 11.1 Access to adequate, safe, and affordable housing and basic services and slum upgrading, with RII (0.787). This study offers insight into their combined efforts toward achieving inclusive, resilient, and sustainable urban development for policymakers, scholars, and practitioners. Additionally, it promotes SDG 11 by highlighting avenues for further study, knowledge sharing, and cooperation.